Assessment of Genetic Diversity in Ethiopian Sesame (Sesamum indicum L.) Germplasm using Random Amplified Polymorphic DNA (RAPD) Markers (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Genetic diversity among 128 sesame (Sesamum indicum L.) genotypes representing 10 geographically distinct populations in Ethiopia was assessed at DNA level using RAPD analysis. Eleven RAPD primers used amplified a total of 149 bands, of which 142 (95. 45%) were polymorphic. Each primer generated 7 to 23 amplified fragments with an average of 13.5 bands per primer. Percent of polymorphic loci (P%), number of different (Na) and effective (Ne) alleles along with Shannon information index (I) and Neiâ€™s gene diversity (He) values suggested that the population of Oromia was the most diverse of all populations, while populations from Afar (cultivars) and AM-NSh were found to be the least diverse. Based on average dissimilarity values obtained with RAPD primers, AM-NG-25, SNNP-7 and SNNP-8 were the most distinct of all genotypes, while genotypes ORO-20 and TIGR-5 showed maximum similarity with others. The UPGMA clustering based on the dissimilarity matrix clustered the genotypes into 3 major groups and 11 subgroups, while three genotypes viz., BENSH-6, ORO-14 and SNNP-5 were found out-grouped from the rest and did not join any of the cluster; they are then most divergent genotypes. Generally, both clustering and PCoA patterns revealed that most genotypes located geographically far apart were found to cluster in the same group, while those genotypes from the same origin dispersed. Overall results indicated that RAPD technique revealed a high level of genetic variation among sesame genotypes collected from diverse ecologies of Ethiopia.Â